Developing Global Competencies in Teacher Education for 21st Century Learning Environments - Syafi’i, Asrop; 'Azah, Nur; Arifin, Zainur; Ibnu Sholeh, Muh; Ayu Tasya, Dinar (Journal of Teaching and Learning, 2024)
Incorporating global competencies into teacher training is a vital strategy to equip educators with the skills necessary to meet the demands of 21st-century classrooms. These competencies—such as global awareness, intercultural communication, critical thinking, and cross-cultural understanding—play a crucial role in creating inclusive and dynamic learning environments. This study adopts a library research approach, analyzing various academic sources, journals, and reports relevant to teacher training and the development of global competencies. The research aims to emphasize the significance of these competencies in teacher preparation, explore effective teaching methods, identify challenges in implementation, and assess their effects on both educators and students. The findings indicate that experiential learning and the integration of educational technology are among the most effective strategies for fostering global competencies in teacher training programs. Despite these advances, obstacles such as limited resources, inadequate funding, and a shortage of qualified trainers remain challenges. Teachers who complete this training demonstrate better management of classroom diversity and are more adept at teaching global issues. Students taught by these educators show improvements in critical thinking and social empathy. This study highlights the need for policies that support global competency-based teacher training, the creation of interactive training materials, and the promotion of international collaborations. The results suggest that a comprehensive approach to educational reform is essential for preparing teachers to meet the evolving needs of contemporary classrooms and to build inclusive, sustainable societies.